COVID-19 vaccine acceptance among pregnant women: a hospital-based cross-sectional study in Sudan - Omar, Saeed M.; Osman, Osama S.; Khalil, Rehana; Al-Wutayd, Osama; Adam, Ishag (Frontiers in Public Health, 2023)
Introduction Pregnancy increases the risk of developing a severe illness due to COVID-19 infection. To the best of our knowledge, no previous study has been conducted on COVID-19 vaccine acceptance among pregnant women in Sudan. Hence, this study aimed to determine COVID-19 vaccination acceptance and its predictors among pregnant women. Methods A cross-sectional study was conducted among 623 pregnant women attending Gadarif maternity hospital in eastern Sudan through a structured questionnaire. Data were obtained on sociodemographic characteristics, obstetric and health-related characteristics, COVID-19 infection, and vaccination-related information, as well as beliefs about and acceptance of COVID-19 vaccination. Results COVID-19 vaccine acceptance among the pregnant women was 2.7%. The vaccine acceptance was higher if their husband’s education was secondary school or higher [adjusted odds ratio [AOR] 4.30, 95% confidence interval (CI) 1.11–16.65, p = 0.035] and discussion of COVID-19 vaccine with the pregnant women by a health care professional in the hospital (AOR 5.46, 95% CI 1.94–15.35, p < 0.001). The most common reasons for resistance to the vaccine were concerns about the side effects of the vaccine for the mother and her baby. Conclusion Acceptance of the COVID-19 vaccination among the pregnant women was very low. Discussions with pregnant women and their husbands by health care professionals regarding the safety of COVID-19 vaccine for the mother and her baby are highly recommended.